Occurrence of Gastritis Is Related to Stress among Health Science Students - Haryanik, Meilinda Alya' Putri; Istiaji, Erdi (Faculty of Medicine Universitas Padjadjaran, 2025)
Background: Gastritis is among the top 10 health issues in Indonesia, with stress as the primary factor. Stress can put students at risk, leading to stress management neglect. This study aimed to find the relationship between stress and the occurrence of gastritis among students, especially those majoring in Health Sciences.Methods: This was a retrospective cohort study conducted in October 2022–March 2023 on 273 Health Science students at the University of Jember, Indonesia, using a simple random sampling method. Data on suspected gastritis occurrence with stress was analysed, using the Spearman's rank correlation test.Results: The majority of respondents were female (84.2%) aged 22 years (50.2%) and were at the post-proposal seminar stage (55.7%). Stress level was moderate (41.8–46.9%). There was a relationship between the type of stress and the suspected gastritis occurrence (p<0.05). The type of stress that was strongly associated with suspected occurrence of gastritis was social-related stressor (r= 0.316).Conclusions: The study highlights the impact of stress on physical health and encourages the use of mental health services on campus to prevent and address related issues. Further studies are needed to explore other contributing factors. A better healthy lifestyle among students with health sciences background is recommended